Expression of Three Related to ABI3/VP1 Genes in Medicago truncatula Caused Increased Stress Resistance and Branch Increase in Arabidopsis thaliana - Wang, Shumin; Guo, Tao; Wang, Zhen; Kang, Junmei; Yang, Qingchuan; Shen, Yixin; Long, Ruicai (Frontiers in Plant Science, 2020)
Related to ABSCISIC ACID INSENSITIVE3 (ABI3)/VIVIPAROUS1(VP1)(RAV) transcription factors, which encode a B3 domain and an APETALA2(AP2) domain, belong to the APETALA2/ethylene-responsive element binding factor(AP2/ERF) or B3 superfamily and play an important role in regulating plant growth and development and responding to abiotic stress. Although there have been many functional studies on RAV, the functional differences between RAVs are not clear. Therefore, in this study, the functional differences of RAVs of Medicago truncatula were analyzed. Based on sequence data from the plant transcription factor database and the M. truncatula genome database, we cloned three RAV genes from M. truncatula, named MtRAV1, MtRAV2, and MtRAV3. The cis-acting elements of these genes promoters were predicted, and the expression patterns of MtRAVs under exogenous conditions (4℃, NaCl, Polyethylene Glycol, Abscisic acid) were analyzed. MtRAVs transgenic Arabidopsis thaliana were obtained and subjected to adversity treatment. Subcellular localization results indicated that MtRAVs were located in the nucleus. A much lower expression level was observed for MtRAV3 than the levels of MtRAV1 and MtRAV2 in M. truncatula for growth in normal conditions, but under 4℃ or PEG and NaCl treatment, the expression level of MtRAV3 was significantly increased. Only the MtRAV3 overexpression transgenic plants showed strong cold resistance, but the overexpressed MtRAV1 and MtRAV2 transgenic plants showed no difference from wild type plants. MtRAV transgenic plants exhibited similar response to exogenous mannitol, NaCl, and ABA, and the expression of some adverse-related marker genes were up-regulated, such as COLD REGULATED 414 THYLAKOID MEMBRANE 1 (COR414-TM1), Arabidopsis thaliana drought-induced 21 (AtDI21), and Arabidopsis thaliana phosphatidylinositol-specific phospholipase C (ATPLC). MtRAVs transgenic Arabidopsis thaliana exhibited increasing of branch number. These results indicated that there was some function redundancy during MtRAVs proteins of M. truncatula, and MtRAV3 has increased function compared to the other two genes. The results of this study should provide the foundation for future application of MtRAVs in legumes.